Recurrent reactive hypoglycemia due to clozapine‐induced glucose intolerance: A case report - Fumihiko Kawai; Satsuki Watanabe; Hirotaka Ebihara; Naoki Shimizu; Shiori Oshima; Hiroshi Okai; Yoshiko Murata; Hisatoshi Arai; Koji Matsuo (PCN Reports, 2023)
Abstract Background Although diabetes is one of the most common side effects of clozapine, a medication for the treatment of schizophrenia, to the best of our knowledge no study exists on clozapine‐induced glucose intolerance or hypoglycemia in patients with schizophrenia. Case Presentation We report a case of schizophrenia with repeated reactive hypoglycemia due to abnormal glucose tolerance during clozapine treatment. During clozapine administration in patients with schizophrenia, it is necessary to monitor physical and psychiatric symptoms due to reactive hypoglycemia and hyperglycemia. If abnormal glucose tolerance is a concern, it should be promptly detected using blood or oral glucose tolerance tests. Conclusion Early intervention for impaired glucose tolerance may prevent clozapine discontinuation due to diabetes or hyperglycemia.